2022
DOI: 10.1007/s00432-022-04254-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating circular RNA hsa_circ_0023179 acts as a diagnostic biomarker for non-small-cell lung cancer detection

Abstract: Background: Lung cancer, the most prevalent cancer-related death worldwide, still lacks the means for early diagnosis. Because of the unique properties of the loop that make it stable in body uids, circular RNAs (circRNAs) as a biomarker becomes a possibility. This research purposed to explore whether hsa_circ_0023179 can be applied as a possible biomarker for the early diagnosis and prognosis of non-small cell lung cancer (NSCLC).Methods: hsa_circ_0023179 was screened by high-throughput sequencing of three pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A F-circEA, a circRNA generated by EML4-ALK fusion gene, is another potential liquid biopsy biomarker as it specifically exists in the plasma of EML4-ALK-positive NSCLC patients and contributes to tumor development by promoting cell migration and invasion ( Tan et al, 2018 ). An investigation into NSCLC diagnostic potential of a circulating circular RNA hsa_circ_0023179 revealed that its higher expression was connected to histological type, TNM stage, lymph node metastasis, and distal metastasis in NSCLC tissue, serum and cells ( Zhang et al, 2023 ). Moreover, it showed higher sensitivity and specificity when compared to traditional tumor markers.…”
Section: Role Of Circrnas In Lung Cancermentioning
confidence: 99%
“…A F-circEA, a circRNA generated by EML4-ALK fusion gene, is another potential liquid biopsy biomarker as it specifically exists in the plasma of EML4-ALK-positive NSCLC patients and contributes to tumor development by promoting cell migration and invasion ( Tan et al, 2018 ). An investigation into NSCLC diagnostic potential of a circulating circular RNA hsa_circ_0023179 revealed that its higher expression was connected to histological type, TNM stage, lymph node metastasis, and distal metastasis in NSCLC tissue, serum and cells ( Zhang et al, 2023 ). Moreover, it showed higher sensitivity and specificity when compared to traditional tumor markers.…”
Section: Role Of Circrnas In Lung Cancermentioning
confidence: 99%
“…Hang D. et al [113] adopted RNA sequencing (RNA-seq) and qRT-PCR approaches to explore cancer-related circRNAs expression, showing that circFARSA was increased in cancerous tissues, and was more abundant in the plasma of LC patients than controls. Other three circRNAs were tested as potential biomarkers for LC early detection with liquid biopsy showing a good diagnostic accuracy: hsa_circ_0023179 [114], hsa_circ_0006423 [115] and circFOXP1 [116].…”
Section: Circular-rnas (Circ-rnas)mentioning
confidence: 99%